Ultrastructure of mice testes affected by orally administered crocin of crocus sativus - Al-Fartwsy, ARH; Mohammadpour, AA; Parham, A (Journal of the Hellenic Veterinary Medical Society, 2024)
In this study, thirty-two adult male mice were divided into four groups control and experimental treatment groups received crocin at 4, 20, and 100 mg/kg daily for six weeks. In results, testosterone level was increased significantly from 18.5 ng/dl in the control to 49.3 ng/dl in group received crocin at 20 mg/kg. The regular features of seminiferous tubules with increased Sertoli cells have been observed in the 20mg/kg crocin group. In the group received crocin at 100 mg/kg, many of the seminiferous tubules were atrophic, spermatogenic cells were discontinuous in the same areas while the space among them has been increased, and fewer interstitial tissue between seminiferous tubules were observed. The changes were markedly advanced by increasing the number of atrophied seminiferous tubules. Electron microscopic results showed the large mitochondria with normal crista and dilated rough endoplasmic reticulum in spermatid cells of the 20 mg/kg crocin group. In the 100 mg/kg crocin group, most of the cell cytoplasm showed vacuolated mitochondria with patchy matrix and distorted vision cristae, with many lysosomes, lipid droplets and vacuoles. Some sperms had abnormal swollen nuclear and irregular wavy acrosomal system. The results of the present study showed that crocin at 20 mg/kg has a protective effect on the germinal epithelium of seminiferous tubules while at 100 mg/kg had destructive effects on the histological structure of the treated mice testicles. In conclusion, treating healthy male mice with crocin for six weeks increased the testosterone concentration while at 100 mg/kg damaged the testicle’s structure